Masque, Da’wa, and Social Resilience: Study of the Integration of the Sampangan Mosque Surakarta - Mibtadin, Mibtadin (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
A mosque is commonly known as a place for Muslim to do pray. Sampangan mosque has been multifunctional as spiritual and non-spiritual development of the society as so far, particularly in the form of empowerment and strengthening the social defense from radical religious movements. How about society empowerment carried out by the Sampangan mosque in Pasar Kliwon Surakarta improving the social and religious resilience of the community? This research is a qualitative descriptive, data collection is done through observation; deep interview; and documentation on community empowerment and strengthening the social defense of the community from radical religious movement. Data analysis uses an interactive analysis model of data reduction, displaying data, and conclusions. society empowerment through the Sampangan mosque in Surakarta is indirectly to improve the social life of worshipers and society. Empowerment through the Sampangan mosque strengthens the capacity, the aspects of education, economics, health, and moderate religious narratives to strengthen the resilience of the community from radical religious movement by assisting the community.